POLITICAL TRANSFORMATION OF THE MIDDLE EAST AFTER THE FIRST WORLD WAR - Tsisnami Chikaidze (Гуманитарные и юридические исследования, 2021)
In the historical context the formation of many contemporary Middle East states was due to the collapse of the Ottoman Empire into constituent parts. The crash of the Turkish domination was result of the weakening of the empire under the pressure of the powers of the Entente seeking to receive control over its possession and the rise of the national liberation movement. The victorious powers in the current situation were guided by the policy of dividing the Arab world into state entities. The transition of the Middle East region from the condition of cultural decline to the condition of political dissociation turned out to be the consequence of implementation of the Sykes-Picot Agreement. The peculiarity of the national liberation movement of that period occurring in the face of opposition of Britain and France, was the co-existence of centripetal and centrifugal tendencies. However, the tendency towards unity, particularly in the face of Western political and economic pressure, was a part of the national mindset of the Arab world.